Exploring the carcinogenic potential of bisphenol A in lung adenocarcinoma: molecular mechanisms, key gene insights, and immune microenvironment impacts - Chen, Haizhu; Jiang, Tiancheng; Yang, Yihan; Cai, Gengyi; Jiang, Yupeng; Ouyang, Wenhao (Frontiers in Immunology, 2025)
BackgroundBisphenol A (BPA) is an endocrine-disrupting chemical that may contribute to cancer development. However, its role in lung adenocarcinoma (LUAD) remains poorly understood. This study aimed to investigate how BPA affects LUAD development by examining key genes involved in tumor progression and the immune microenvironment.MethodsNetwork toxicology, molecular docking, and clinical data analyses were performed to identify potential molecular targets of BPA in LUAD. Common genes between BPA targets and LUAD biomarkers were screened, and their biological significance was evaluated through survival analysis, immune infiltration assessment, and protein–ligand interaction studies.ResultsA total of 218 overlapping genes were identified between BPA targets and LUAD biomarkers, including BUB1, BUB1B, CCNA2, CDK1, and UBE2C. These genes were strongly associated with LUAD progression, poor survival outcomes, and enhanced immune cell infiltration. Molecular docking revealed strong binding affinities between BPA and these proteins, suggesting potential disruption of their normal biological functions.ConclusionThis study provides valuable insights into the potential risks of BPA exposure in LUAD. The identified key genes and pathways may serve as potential biomarkers and therapeutic targets, offering new directions for future research and public health strategies.